2008
DOI: 10.1523/jneurosci.5421-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interaural Level Difference Discrimination Thresholds for Single Neurons in the Lateral Superior Olive

Abstract: The lateral superior olive (LSO) is one of the earliest sites in the auditory pathway that is involved in processing acoustical cues to sound location. Here, we tested the hypothesis that LSO neurons can signal small changes in interaural level differences (ILDs), a cue to horizontal sound location, of pure tones based on discharge rate consistent with psychophysical performance in the discrimination of ILDs. Neural thresholds for ILD discrimination were determined from the discharge rates and associated respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 65 publications
3
42
0
Order By: Relevance
“…Given that neurons will differ in their firing rates across any type of map, the absolute firing rates may not be of significance. The azimuth locations around which each neuron provides maximum information (partly dependent on the azimuth of the steepest ARF slope) will be of significance (Harper and McAlpine 2004; Jazayeri and Movshon, 2006; Tollin et al, 2008). This depends on the shape of the ARF, and not on the absolute firing rates.…”
Section: Discussionmentioning
confidence: 99%
“…Given that neurons will differ in their firing rates across any type of map, the absolute firing rates may not be of significance. The azimuth locations around which each neuron provides maximum information (partly dependent on the azimuth of the steepest ARF slope) will be of significance (Harper and McAlpine 2004; Jazayeri and Movshon, 2006; Tollin et al, 2008). This depends on the shape of the ARF, and not on the absolute firing rates.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency response area is the 2D pattern of spike counts as a function of frequency and level. Best frequencies were derived offline using the automated method described previously (Palmer et al, 2013;Sumner and Palmer, 2012) with visual confirmation.…”
Section: Methodsmentioning
confidence: 99%
“…Park et al (1997) found that characteristic ILDs are independent of the excitatory stimulus level in the LSO but not the ILDs associated with the 50% response rate. Although responses at the threshold and slope of a tuning curve both provide information about stimuli (Seung and Sompolinsky 1993;Tollin et al 2008), the level-invariant feature associated with characteristic ILD is more desirable for encoding ILDs when the overall sound level is not static.…”
Section: Balanced Excitation and Inhibition For "Characteristic" Ildsmentioning
confidence: 99%